2018
DOI: 10.1186/s12955-018-0955-2
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of pain catastrophizing in health-related quality of life judgments after Total knee arthroplasty

Abstract: BackgroundTotal knee arthroplasty (TKA) is a highly effective procedure that yields reductions in pain and disability associated with end stage osteoarthritis (OA) of the knee. Quality of life instruments are frequently used to gauge the outcomes of total knee arthroplasty (TKA). However, research suggests that post-TKA reductions in symptom severity may not be the sole predictors of quality of life post-TKA. The primary objective of the present study was to examine the prognostic value of catastrophic thinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 53 publications
3
13
0
2
Order By: Relevance
“…Overall, our results correlate with a previous study from Dunn et al [17] that identified catastrophization, anxiety and depression as important players in modulating postoperative pain. Our results point in the same direction as Yakobov et al [23] who noted that pain catastrophization correlated significantly to the postoperative Health-Related Quality of Life (HRQoL) over other variables (demographic variables, co-morbid health conditions, baseline HRQoL, and postoperative reductions in pain, joint stiffness and physical disability). A similar trend was observed by Wright et al [24] supporting that catastrophizers (PCS > 30) would be more likely to have a longer length of stay after total joint surgery.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, our results correlate with a previous study from Dunn et al [17] that identified catastrophization, anxiety and depression as important players in modulating postoperative pain. Our results point in the same direction as Yakobov et al [23] who noted that pain catastrophization correlated significantly to the postoperative Health-Related Quality of Life (HRQoL) over other variables (demographic variables, co-morbid health conditions, baseline HRQoL, and postoperative reductions in pain, joint stiffness and physical disability). A similar trend was observed by Wright et al [24] supporting that catastrophizers (PCS > 30) would be more likely to have a longer length of stay after total joint surgery.…”
Section: Discussionsupporting
confidence: 88%
“…The amygdala also appears to modulate affective abnormalities associated with chronic pain, such as catastrophizing, through exaggerated and abnormal functional connectivity with the central executive network (88). This is important because catastrophizing can further exacerbate chronic pain conditions and increase the likelihood of poor clinical outcomes (89,90). Similar to the observations in patients with chronic pain, studies have found that using oral morphine for 1 month leads to persistent decreases in amygdala gray matter volume (91).…”
Section: Amygdalamentioning
confidence: 86%
“…Literatürdeki çalışmalar incelendiğinde, diz protezi uygulanan hastaların ağrı puan ortalamalarının 2-4 arasında değiştiği gözlenmektedir. 10,17 Bu araştırmada, hastaların eğitim durumuna göre ağrı puan ortalamaları arasındaki fark istatistiksel olarak anlamlı bulundu (p<0,05). Eğitim düzeyi sadece okuryazar olanların ağrı puan ortalamasının, diğer gruplara oranla anlamlı derecede yüksek olduğu belirlendi (Tablo 4).…”
Section: Discussionunclassified
“…2 Cerrahi girişim uygulanan hastalarda olduğu gibi, total diz protezi (TDP) uygulanacak hastalarda da komplikasyon gelişme riski, fonksiyonlarını kaybetme düşüncesi, ameliyat sonrası ağrı, öz bakım yetersizliği, düşme endişesi ile ölüm düşüncesi gibi nedenlerle kaygı ve korku duydukları belirtilmektedir. [8][9][10] TDP; ağrıyı gidermek, hareketliliği ve stabiliteyi sağlamak, deformiteyi düzeltmek, eklem çizgisinin korunması, bağ dengesinin sağlanması, komşu eklemlerde ağrılı sekonder etkilerin önlenmesi ve giderilmesi amacıyla uygulanan cerrahi girişim-lerden biridir. 11 Osteoartritli hastalarda şiddetli ağrı varlığı, TDP uygulanması için bir endikasyon olarak belirtilmektedir, ancak TDP ameliyatları yüksek derecede ağrıya neden olan ameliyatlardan biridir.…”
unclassified